Subsurface Characterization Using Cone Penetration Test Data for Pile Group Performance Evaluation - Nguyen QH Qh; Nam Nguyễn; Chieu Vu Dinh (Momentum International Journal of Civil Engineering (MIJCE), 2026)
Subsurface characterization plays a critical role in foundation planning, particularly in areas with weak soil conditions where accurate assessment of soil behavior is required to ensure structural stability. This study aims to evaluate the influence of pile group configuration on pile efficiency and bearing capacity using Cone Penetration Test (CPT) data as the primary source of subsurface information. The research employed a quantitative analytical approach based on CPT-derived soil parameters, where single-pile capacity was calculated using the Direct Method and group-pile capacity was determined through pile efficiency factors. Several pile group configurations consisting of three and four piles were modeled and compared to identify the most effective arrangement. The results indicate that pile group configuration significantly affects pile efficiency and overall bearing capacity. Configurations with higher efficiency factors produced greater allowable group capacities, demonstrating a direct relationship between pile arrangement and foundation performance. The highest efficiency values reached 0.861 for three-pile configurations and 0.844 for four-pile configurations, resulting in improved bearing capacities compared with conventional arrangements. These findings highlight the importance of integrating CPT-based subsurface characterization into foundation design and engineering surveying practices. It is recommended that pile group layouts be optimized during the planning stage to maximize load-bearing performance and minimize potential settlement. The study contributes to geotechnical surveying applications by demonstrating the value of CPT data in supporting evidence-based foundation design decisions.